2009
DOI: 10.1118/1.3266769
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of a novel four‐dimensional diode array

Abstract: With the proposed calibration method and the automatic gantry angle derivation algorithm, the 4D diode array achieved isotropic detector response and is suitable for both IMRT and rotational therapy pretreatment verification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 31 publications
2
65
0
Order By: Relevance
“…We performed an in‐house calibration following manufacturer procedures for each beam energy utilized clinically for IMRT or VMAT plans (6, 15, and 18 MV). The first step is the detector array calibration, which measures and corrects for the relative sensitivity of the detectors 13 , 19 . This calibration is intended to be applied to the raw measurements of each detector to eliminate relative response differences between individual detectors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed an in‐house calibration following manufacturer procedures for each beam energy utilized clinically for IMRT or VMAT plans (6, 15, and 18 MV). The first step is the detector array calibration, which measures and corrects for the relative sensitivity of the detectors 13 , 19 . This calibration is intended to be applied to the raw measurements of each detector to eliminate relative response differences between individual detectors.…”
Section: Methodsmentioning
confidence: 99%
“…In the past five years, several studies reported experience with the ArcCHECK 13 , 14 , 15 , 16 . Yan et al (13) reported on developing a calibration procedure for the detector array to account for both the intrinsic differences between the detectors, as well as correcting for any angular dependence.…”
Section: Introductionmentioning
confidence: 99%
“…( 19 ) The angular response dependency calibration of the ArcCHECK system has been performed by Yan et al ( 20 ) However, the diodes are designed and embedded in a nonisotropic structure, and a noncoplanar radiation delivery can exhibit some angular dependency. In this study, we investigated the impact of the angular dependency on the gamma passing rate for the noncoplanar delivery, which has not been evaluated previously.…”
Section: Introductionmentioning
confidence: 99%
“…It can be employed by itself to compare measured and reference dose at the detectors’ locations 1 , 2 , 3 , 4 , 5 , 6 or in conjunction with 3DVH software (Sun Nuclear) that uses a AC‐based planned dose perturbation (ACPDP) algorithm to perform volumetric measurement‐guided dose reconstruction on a phantom or patient dataset 7 , 8 , 9 , 10 , 11 . While the dosimeter and associated software have been characterized and employed rather extensively, (1–3,5,7,9,10,12–18) two recent developments necessitated revisiting the subject.…”
Section: Introductionmentioning
confidence: 99%